American literature in context after 1929 - Yannella, Philip; Yannella, Philip (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2011)
This text situates American literature from the Great Depression to the present day in its historical context. It draws on a range of documents from magazine and newspaper accounts to government reports and important non-fiction.
Timeline of texts and historical events -- Introduction -- The depression and the early 1940s -- Anti-communism -- Bad and mad -- Places -- Immigrant destinies.
Continues the author's: American literature in context from 1865 to 1929.
Includes bibliographical references and index.
Keywords: American literature -- 20th century -- History and criticism; National characteristics, American, in literature; Literature and history -- United States -- History -- 20th century; American literature; Literature and history; National characteristics, American, in literature; United States; 1900-1999; Criticism, interpretation, etc; History